2013
DOI: 10.1177/0009922813510204
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Late-Onset Hearing Loss in Infants With Congenital Cytomegalovirus Infection

Abstract: In children with late-onset hearing loss due to cytomegalovirus infection, antiviral treatment appears to prevent further deterioration and produce improvement. Controlled studies are needed to verify this observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 15 publications
1
30
0
6
Order By: Relevance
“…Начало антивирусной терапии в возрасте старше 30 дней жизни считается не эффективным [40], хотя ряд авторов свидетельствует обратное [41,42]. В исследованиях Amir J. et.…”
Section: лечениеunclassified
“…Начало антивирусной терапии в возрасте старше 30 дней жизни считается не эффективным [40], хотя ряд авторов свидетельствует обратное [41,42]. В исследованиях Amir J. et.…”
Section: лечениеunclassified
“…Despite many case reports and cohort studies, data from only 2 RCTs on antiviral treatment for cCMV have been published [ 12 , 13 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. A phase III RCT, primarily assessing the hearing outcomes of newborns with cCMV, was conducted by the National Institute of Allergy and Infectious Diseases Collaborative Antiviral Study Group (CASG) [ 12 ].…”
Section: Benefit Of Antiviral Therapymentioning
confidence: 99%
“…The highest quality evidence available is limited to retrospective case series of small numbers of babies treated outside the newborn period. Amir et al [ 68 ] reported on 21 children, the majority of which had asymptomatic cCMV or only lenticulostriatal vasculopathy, which were treated with antivirals over a 9 to 12 month period starting at a median age of 8 months. At the last follow-up (median age of 24 months), hearing impairment improved in 29 of 35 ears evaluated.…”
Section: Benefit Of Antiviral Therapymentioning
confidence: 99%
“…Во время проведения аудиологического скрининга новорожденных с бессимптомной формой врожденной ЦМВИ в раннем послеродовом периоде методом отоакустической эмиссии и регистрации слуховых вызванных потенциалов такие дети, как правило, показывают нормальные результаты. Развитие прогрессирующей СНТ часто является первым симптомом наличия ЦМВИ [24]. Средний возраст выявления тугоухости на первом году жизни составляет 7,4±3,7 мес [24].…”
unclassified
“…Развитие прогрессирующей СНТ часто является первым симптомом наличия ЦМВИ [24]. Средний возраст выявления тугоухости на первом году жизни составляет 7,4±3,7 мес [24]. Однако нарушение слуха может обнаруживаться и в более поздние сроки, при этом средний возраст манифестации СНТ при инаппарантной форме ЦМВИ составляет 44, а при клинической -33 мес [25].…”
unclassified